Impregnation of palm shell-based activated carbon with sterically hindered amines for CO2 adsorption - Lee, C.S.; Ong, Y.L.; Aroua, M.K.; Daud, W.M.A.W. (Elsevier, 2013)
In this work, equimolar amounts of three types of sterically hindered amines (e.g. 2-amino-2-methyl-1,3-propanediol, 2-amino-2-methyl-1-propanol and 2-(methylamino)ethanol) were impregnated onto the surface of palm shell-based activated carbon. Breakthrough curves of CO2 adsorption were determined using a continuous gas-solid adsorption column. Effects of the type of amine and gas flow rates on the breakthrough time were studied. The results showed that impregnated activated carbon have higher adsorption capacity than virgin activated carbon despite the dramatic decrease in surface area during impregnation. Among the three investigated amines, 2-amino-2-methyl-1-propanol showed the highest bed adsorption capacity.